Expanding the Unidirectional View on Parental Television Mediation: Children’s Guidance of Their Parent’s Television Use - Nelissen, Sara; Van den Bulck, Jan (Journal of broadcasting & electronic media, 2018)
Compared to parental mediation research, much less is known about how children influence and guide their parents' media use. This study examined whether children also mediate the television use of their parents. Measures of an existing television mediation scale were reversed to the perspective of the child guiding the parent's television use. A sample of 187 parent-child dyads completed a cross-sectional survey in Flanders (Belgium). Factor analyses showed that the original subscales were reproduced with high internal validity. Both parents and children had congruent views about children's television mediation; television mediation and children's restrictive mediation was positively associated with conflict in the family.